Clinical Presentation with Predictors of Severity of Dengue Fever in Children of 2019, Endemic in Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Dengue fever is a serious public health problem with a wide range of clinical manifestations. In 2019, the clinical presentation of dengue infection was novel in relation to the conventional features of the previous years and also in degree of severity. So the study was done to see the varied clinical presentation, predictors of severity and outcome in pediatric population in 2019 endemic.Methods: It was a cross sectional, descriptive study conducted among 100 cases of serologically positive dengue patients from department of Paediatrics of Shaheed Suhrawardy Medical College Hospital, Dhaka from July to October, 2019.The data were collected by preformed semi-structured questionnaires and analyzed using SPSS version 16.0.Results: The mean age of the patients was 7.4 ± 3.4 years with equal male and female ratio. Children between 5-12 years were most (72%) commonly affected. Mean duration of fever was 4.5 ± 1.8 days and fever was present in 63% cases on presentation. Features of shock were present in 61% of patients who were designated as severe dengue. Most of the patients presented with abdominal pain (77%) followed by vomiting (70%), headache (35%), myalgia(32%) and retro-orbital pain(30%). Among the important clinical findings, tender hepatomegaly was present in 77% cases followed by ascites in 35% and pleural effusion in 4% cases. Melaena was found to be the most common form of bleeding manifestation. Risk factors for severe dengue were vomiting, abdominal pain, melaena, ascites and low platelet count. Majority of the patients (95%) were discharged, 4% were referred to ICU and only 1% died.Conclusion: Majority of admitted pediatric dengue patients presented with severe Dengue (Dengue Shock Syndrome). Presence of vomiting, abdominal pain, ascites and low platelet count were found to be significant in predicting severity of dengue.J Shaheed Suhrawardy Med Coll 2021; 13(1): 8-14